The Islamic Court Resilience and Digital Disruption : A Prospective Review of The Indonesian Religious Courts - Zulkarnain, Zulkarnain; Hidayat, Syamsul (Indonesian Journal of Islamic Economic Law, 2026)
The background of this research stems from the urgent need to ensure the adaptability and institutional resilience of religious courts amid digital disruption. The purpose of this research is to develop a theory of prospective resilience of religious court institutions by tracing the historical foundations and legal frameworks that shape institutional resilience in the face of technological transformation. This research is qualitative in nature with a legal-historical and juridical-normative approach. Data were collected through a document study of regulations on the institutionalization of religious courts and legal literature on judicial institutions, then analyzed using content analysis and interpretive-historical methods. The results of the study show that the prospective resilience of religious courts is built on three dimensions: continuity of Islamic legal values, the recontextualization of justice norms within the digital system, and the integration of ethical responsibility principles into the use of AI. The novelty of this research lies in the development of institutional resilience theory rooted in legal-historical methodology, which places institutional history as the conceptual foundation for the resilience and legitimacy of religious courts in the era of digital disruption.